Hypoactivity and neurochemical alterations in the basal ganglia of female Sprague-Dawley rats after repeated exposure to atrazine - Acevedo-Huergo, Triana; Sánchez-Yépez, Jonathan; Mendoza-Trejo, María Soledad; Hernández-Plata, Isela; Giordano, Magda; Rodríguez, Verónica Mireya (Frontiers in Toxicology, 2024)
The herbicide atrazine (ATR) has been one of the most widely used herbicides worldwide. However, due to its indiscriminate use, it has been considered an environmental contaminant. Several studies have classified ATR as an endocrine disruptor, and it has been found to have neurotoxic effects on behavior, along with alterations in the dopaminergic, GABAergic, and glutamatergic systems in the basal ganglia of male rodents. These findings suggest that these neurotransmitter systems are targets of this herbicide. However, there are no studies evaluating the neurotoxicity of ATR in female rodents. Our study aimed to assess the effects of repeated IP injections of 100 mg ATR/kg or a vehicle every other day for 2 weeks (six injections) on the locomotor activity, content of monoamines, GABA, glutamate, and glutamine in the striatum, nucleus accumbens, ventral midbrain, and prefrontal cortex, and tyrosine hydroxylase (TH) protein levels in striatum and nucleus accumbens of female rats. Repeated 100 mg ATR/kg injections immediately decreased all the locomotor activity parameters evaluated, and such hypoactivity persisted for at least 48 h after the last ATR administration. The ATR administration increased dopamine and DOPAC content in the nucleus accumbens and the dopamine and DOPAC and serotonin and 5-HIAA content in the ventral midbrain. In contrast, the TH protein levels in the striatum and nucleus accumbens were similar between groups. Meanwhile, GABA, glutamine, and glutamate levels remained unaltered in all brain regions evaluated. The observed behavioral alterations could be associated with the monoamine changes presented by the rats. These data reveal that the nucleus accumbens and ventral midbrain are susceptible to repeated ATR exposure in female rats.